Treponema denticola Is Resistant to Human β-Defensins - Brissette, Catherine A. (American Society for Microbiology, 2002)
Spirochetes, including Treponema denticola, are implicated in the pathogenesis of periodontal disease. Because T. denticola lacks lipopolysaccharides that serve as targets for human β-defensin (hβD) binding, we postulated that T. denticola would resist killing by hβD. We showed that T. denticola is resistant to hβD-1 and -2. Protease inhibitors did not enhance killing of T. denticola by hβD-2, suggesting that degradation of hβD-2 by treponemal proteases is not a major factor in T. denticola resistance.